Wettability of Dendrocalmus asper under Various Heating Time during Composites Making Process. Issue 1 (September 2021) - Baiti, Risa Nurin; Maulana, Sena; Mangurai, Silvia Uthari Nuzaverra Mayang; Murda, Rio Ardiansyah; Bindar, Yazid
Abstract: Bamboos are often used due to their abundance, fast growth rate, cheap price, ductility, and formability in the sector of transportation, musical instrument, cooking ware, etc. For construction purposes, Dendrocalamus asper, (locally known as "Bambu betung"), is used as bamboo composites. The properties of bamboo are highly improved by using phenolic resins (phenol-formaldehyde) as an adhesive in bamboo composites. Bamboo is stronger and more susceptible to any liquid. The liquid is the most common enemy to plant-based structure due to the softening effect. Thus, the wettability of bamboo is an important matter as it indicates the ability of a liquid to spread and penetrate on the surface. The objective of this study was to analyze the effect of various heating times to wettability properties of heat-treated D. asper strands during the bamboo-composite making process. Before testing, the bamboo was cut, cleaned, and sand-grinded. The bamboo strands were heated at 140°C for 1, 2, and 3 hours. Then, the surface of bamboo was evaluated by measuring the contact angle based on the sessile drop method. The constant contact angle was obtained by calculating the regression formula between time (t) and contact angle (θ). The wettability was indicated by the value of K. The color of heat-treated bamboo strands was measured by portable color difference meter model CDX 105 and characterized by CIE Lab. The results showed that the longer the holding time, the surface became more hydrophobic, showed by a highercontact angle. Longer heating gives more time to the resin to spread more evenly into the pores of bamboo so that the hydrophobicity of bamboo composites is increased. The lightness value (L*) of heat-treated bamboo strands tended to decrease with increasing temperature and time of heat treatment. To conclude, for further making the process of bamboo composites using D. asper, we recommend curing the composites for 3 hours.